2021
DOI: 10.1155/2021/3720571
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Diagnostic Value of Quantitative Hepatitis B Virus Core Antibody Test in Chronic Viral Hepatitis B

Abstract: The level of CHB virus (HBV) core antibody (HBcAb) is different in four stages of chronic HBV infection and may be used for differential diagnosis of the natural history of chronic HBV infection. To address this question, we examined multiple blood biomarkers and assessed the efficacy to diagnose different stages of chronic HBV infection. The quantitative detection of HBcAb, hepatitis B surface antigen (HBsAg), HBV DNA, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and platelet count (PLT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Phase 4 was the one that showed a significantly higher mean level than the other three. The phase with the lowest mean value of anti-HBc was phase 1 in all three studies, unlike a more recent study from 2021, which reported a very similar pattern of anti-HBc variations but with the lowest level in inactive phase 3 [ 29 ]. On the other hand, the latest report showed a considerably different way of anti-HBc level changes through phases of infection [ 26 ].…”
Section: Clinical Utility Of Qanti-hbcmentioning
confidence: 52%
See 2 more Smart Citations
“…Phase 4 was the one that showed a significantly higher mean level than the other three. The phase with the lowest mean value of anti-HBc was phase 1 in all three studies, unlike a more recent study from 2021, which reported a very similar pattern of anti-HBc variations but with the lowest level in inactive phase 3 [ 29 ]. On the other hand, the latest report showed a considerably different way of anti-HBc level changes through phases of infection [ 26 ].…”
Section: Clinical Utility Of Qanti-hbcmentioning
confidence: 52%
“…The dynamic of HBcAg expression and its secretion in the serum has yet to be entirely clarified. Still, it is speculated that immune cells are exposed to the immunogenic property of this antigen during cell lysis since numerous studies report a simultaneous increase of anti-HBc antibodies with ALT and aspartate aminotransferase (AST) [ 18 , 20 , 27 , 28 , 29 ]. ALT was used as a surrogate marker of the immune response during CHB because ALT levels were associated with T-cell mediated hepatocyte lysis but had poor specificity since it can be affected by drug and alcohol abuse, fatigue and infection with other hepatotropic viruses [ 56 ].…”
Section: Clinical Utility Of Qanti-hbcmentioning
confidence: 99%
See 1 more Smart Citation
“…We acknowledge that ALT is associated with host innate immunity, and elevated ALT may elicit potent host immunity and shows enhanced therapeutic efficacy [ 28 , 29 ]. However, in this study, the normal and mildly elevated ALT groups achieved similar therapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of HBsAg (qHBsAg) may be helpful for staging HBV infection and predicting its response to antiviral therapy [ 9 ]. According to the results of serology, biochemistry, virology, and other assistant examinations of chronic hepatitis B (CHB) infection, it can be divided into a CHB-carrying state (immune-tolerant phase, IT), inactive HBsAg-carrying state (low-replicative phase, LR), HBeAg- (hepatitis B e antigen-) positive CHB (immune clearance phase, IC), and HBeAg-negative CHB (reactivity period, HBeAg-negative hepatitis, ENH) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%